Infected Hematoma in the Setting of Nonoperatively Treated Proximal Humerus Fracture: A Report of Two Cases. Issue 3 (July 2019) - Blood, Travis D.; Shah, Kalpit N.; Thome, Andrew P.; Mansuripur, Peter K.; Born, Christopher T.; Paxton, E. Scott
Abstract : Case: Two patients presented with infections of their recent proximal humerus fracture sites. These immunocompromised patients were being treated nonoperatively for their proximal humerus fractures; however, both were taken to the operating room for surgical debridement. Conclusions: These 2 cases demonstrate the need for further investigation into infection of closed fracture sites. Attention should be paid to immunocompromised patients who present with proximal humerus fractures, especially displaced 2-part surgical neck fractures with anterior deltoid injury and subsequent hematoma formation. These patients may develop an infection with potential rapid progression to life-threatening septic shock.